Karakteristik Fisiko-Kimia dan Sensori Mayones Mangga Podang Urang Berdasarkan Perbandingan Puree: Susu Full Cream: Physico-Chemical and Organoleptic Characteristics of Podang Urang Mango Mayonnaise Based on Comparison of Puree: Full Cream Milk - Pamujiati, Agustia Dwi; Lisanty, Nina; Azkiyah, Lailatul; Andajani, Wiwiek (Faculty of Agricultural Technology, University of Jember, 2024)
Mango (Mangifera indica L.) is a seasonal tropical fruit and usually harvesting at October until December in Indonesia. In Kediri Regency, one of local variety mango known as ‘Podang Urang’ had been harvested and the production is high. When the harvesting time, the price of ‘Podang Urang’ mango is very cheap around IDR1,600 per kg on wholesale market in Kediri. This condition certainly will adverse the farmers. In order to decrease this risk that faced by farmers, this locally mango could be potential to process as mayonnaise to increase of the price value. This research aimed to process ‘Podang Urang’ mango as mayonnaise, characterize their physicochemical and sensory characteristics, and compare the mayonnaise product as prescribed by the quality requirement criteria of Indonesian National Standard (SNI) No. 01-4473-1998. The mango with 90% maturity was sorted, peelded, and blended. This puree was added with various of full cream milk, citric acid (0.3%), and palm oil (2%) and processed to be mayonnaise. The result showed that the ‘Podang urang’ mango mayonnaise with added with full cream milk (50:50%/B2) had emulsion stability about 99.99%, lightness (L*) of 45.96, protein content of 1.39%, pH of 6.57, vitamin C about 16.43%, and moisture content about 62.67%. This mayonnaise composition (50% of mango puree and 50% of full cream milk) was likely by the panelists in terms of color (7.12), flavor (7.12), taste (7.04), thickness (7.04), and overall acceptable about 7.20. This study provides the utilization of Kediri locally mango (‘Podang Urang’) as a diverse food product, which is acceptable to the panelists and adds value to the raw material. Keywords: diversity of product, local mango, mayonnaise, ‘Podang Urang’